Basic Understanding on How Chat System Works : A Simple Protocol using Java Language - Nahar, H. (LAP LAMBERT Academic Publishing GmbH & Co. KG, 2011)
Nowadays, people are always looking for better and effective ways to communicate with others. This can be achieved by introducing cutting edge technologies such as online chatting instead of a piece of paper. The real and instant interaction solves distance and time consuming matters. This book gives an idea on how the online chatting was developed using a preferable language, Java. A simple protocol scheme has been designed which plays an important element in a way of handling varies types of communications simultaneously. As this application was developed in Java, it can be executed on either Windows or Linux platform. This book is very useful and suitable for all as a ‘kick-start' to know about Chatting World. Features: • The content is explained in simple way and easy to be understood • Describes a project development phase by phase • Provides detail information related to chatting protocol scheme which was designed and implemented in the chatting application. • Give a simple guidance on preparing an executable file to easily run this application on multiplatform.